The effect of microstructure on the thermoelectric properties of Bi2Te3-PbTe alloy - Kwon, O-Jong; Park, Jonglo; Yim, Ju-Hyuk; Koo, Hyun; Kim, Jae-Yeol; You, HyunWoo; Bae, Sung-Hwan; Kim, Jin-Sang; Park, Chan (ELSEVIER SCIENCE BV, 2011)
The microstructures and the thermoelectric properties of the polycrystalline Bi2Te3-PbTe alloy, which was prepared by spark plasma sintering were investigated. The polycrystalline alloy consists of Bi rich and Pb rich regions with several nm sizes, which were identified by transmission electron microscope (TEM) and energy dispersive spectrometer (EDS). The highest power factor, S-2 rho(-1), and ZT value of the polycrystalline alloy were 4.30 x 10(-4) Wm(-1) K-2 and similar to 0.39 at 473 K respectively, and the lowest thermal conductivity was similar to 0.5W/mK at same temperature. The relatively low thermal conductivity of polycrystalline Bi2Te3-PbTe alloy is caused by the increase of grain boundary and interfaces between the Bi-rich and the Pb-rich regions. (C) 2010 Elsevier B. V. All rights reserved.
Keywords: TEMPERATURE; PBTE